Revisiting butafulvene formation by thermal dimerization of fluorene-based dialkynes: effects of aromatic substituents - Schuldt, Moritz P.; Maximenko, Tatjana; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2025)
Butafulvenes, together with pentafulvenes and [3]radialenes, form a series of constitutional benzene isomers in which aromaticity changes significantly and can be strongly substituent dependent. Butafulvene, as a member of this series, is frequently proposed to be antiaromatic. Based on butafulvenes Hopf, Zimmerman and coworkers first time described, derivatives thereof were synthesized and the effects of substituents on both the stability of the intermediate isobenzenes and on their optoelectronic and (anti)aromatic properties are discussed.
Online verfügbar: 27. Oktober 2024
Gesehen am 12.05.2025